Clinical outcomes of circumcisions and prevalence of complications of male circumcisions: A five-year retrospective analysis at a teaching hospital in Ghana. - Sylvester Appiah Boakye; Frank Obeng (PLOS Global Public Health)
Male circumcision is increasing in popularity due to its medical benefits, including reducing HIV prevalence. It is commonly performed by both health and non-health professionals, with most circumcisions occurring during the neonatal period. Studies suggest the benefits outweigh the risks, though complications can occur. This study aimed to determine the clinical outcomes of circumcisions and the prevalence of adverse events of circumcision in the Volta region of Ghana. A five-year retrospective descriptive and analytic study was conducted at Ho Teaching Hospital, using a structured data extraction sheet to collect demographic, clinical, and circumcision-related data from 186 cases. Among 186 circumcision cases, 23 (12.37%) experienced complications, with the most common being partial circumcision (43.48%), post-circumcision bleeding (21.74%), and urethrocutaneous fistula and/or wrongfully circumcised congenital hypospadias (13.04%). Low heamoglobin levels and infections were also noted. A significant relationship was found between the circumcision provider and complication rates (Chi-square = 16.975, p = 0.00). Doctors conducting circumcision had the lowest complication rates (4.3%), while nurses and traditional circumcisers had higher complication rates (39.1% and 34.8%, respectively). Circumcision-Revision surgery was the most common salvage surgery for circumcision mishaps (31.82%), with urethroplasty and hypospadias repair (for wrongful circumcised neonates born with hypospadias) accounting for 15.91%. Meatoplasties, glansplasties, fistulectomy plus primary repair and chordae-release surgeries were also performed. The success rate for salvage surgeries (first attempt) was 70%. Prompt initial management strategies were significantly associated with good outcomes. Under less-trained hands, circumcision could be catastrophic. Salvage surgeries for circumcision mishaps are associated with less favourable outcomes in about one-third of the cases, suggesting that circumcision mishaps are better prevented than salvaged. Training, guidance, and policy interventions are needed to reduce the incidence of circumcision-related mishaps. Public health campaigns to dissuade non-surgeon circumcisers to refrain from circumcising children with hypospadias but refer them, are urgently needed.